The importance of the 3'-enhancer region in immunoglobulin kappa gene expression. - Meyer, K B (1990)
The first enhancers to be identified in the immunoglobulin gene loci are located in the J-C intron. However, deletion of the immunoglobulin kappa intron-enhancer has little effect on the transcription of kappa transgenes. Here we ask whether the second kappa enhancer which we recently identified at the 3'-end of the locus plays a role in kappa gene expression. We show that its omission leads to 20-40 fold lower expression of kappa transgenes and to poor allelic exclusion. Transfection experiments show that activity of the 3'-enhancer, like that of the kappa-intron enhancer, can be induced in a pre-B cell line by incubation with bacterial lipopolysaccharide. Whereas induction of the kappa-intron enhancer is due to induction of NF-kappa B activity, deletion mapping of the 3'-enhancer localises its activity to a 50 nucleotide region that lacks an NF-kappa B site; indeed the 3'-enhancer allows kappa expression in a cell line which lacks NF-kappa B. Thus, both the 3'- and intron-enhancers can be induced at the same stage of differentiation but by distinct pathways. Furthermore, unlike the intron-enhancer, the 3'-enhancer plays a critical role in the transcription of rearranged immunoglobulin kappa genes.